Proceedings of the 9th International Conference for Science Educators and Teachers (ICSET 2017) 2017
DOI: 10.2991/icset-17.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Parents Perception About Sexual Education for Adolescence With Autism

Abstract: This study aims to determine the perception of parents about sexual education given to adolescence with autism. This research is descriptive research with qualitative approach. The subjects of this study were three parents of autistic children who showed a sexual behavior disorder. Data collection using questionnaire and interview method. The results of this study indicate that parents consider adolescence with autism to have sexual development such as adolescents in general despite having a different speed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This result is consistent with the study by Holmes et al (2019) which indicated information about sex education is presented within a limited framework. This finding also aligned with findings by Chamidah and Jannah (2017), which found some parents of adolescents with ASD were knowledgeable regarding sexual development, growth, and sex education.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This result is consistent with the study by Holmes et al (2019) which indicated information about sex education is presented within a limited framework. This finding also aligned with findings by Chamidah and Jannah (2017), which found some parents of adolescents with ASD were knowledgeable regarding sexual development, growth, and sex education.…”
Section: Discussionsupporting
confidence: 87%
“…Parents are the foundation for preparing children with ASD to face these changes and developments (Pryde and Jahoda, 2018;Daghustani and MacKenzie, 2022). Therefore, it is crucial for parents of teenagers with ASD to understand the significance of puberty and be knowledgeable of the changes that occur in their child's sexual development, as well as the difficulties and sexual challenges that may ensue (Chamidah and Jannah, 2017). Parents should learn effective methods and strategies to teach adolescents the concept of sexual functions.…”
Section: Role Of Parentsmentioning
confidence: 99%
See 3 more Smart Citations